A Systematic Review of Work Design: Impact on Employee Performance, Job Satisfaction, and Organizational Outcomes - Fika Rahmanita; Ade Irma Anggraeni; Ratno Purnomo (Citakonsultindo, 2024)
Work design is a key element in human resource management that focuses on designing and organizing tasks to improve employee performance and organizational results. This research conducted a systematic review of 20 international articles to investigate and understand concepts, theories and practices related to work design and their impact on employee performance, job satisfaction and organizational outcomes. The review results show that key elements in work design, such as skill variety, task identity, task significance, autonomy, and feedback, significantly increase employee motivation and engagement. Job characteristics theory, demand-control theory, and socio-technical systems approach are the main frameworks used in previous research to explain how work design can influence various aspects of work. In addition, new approaches such as job crafting and smart work design also show great potential in adapting work to individual employee needs and leveraging modern technology to create a more flexible and adaptive work environment. This research concludes that holistic and integrated job design can improve employee performance and well-being, as well as achieve better organizational outcomes. However, it is important for organizations to consider the balance between the benefits of technology and its impact on employee wellbeing. By understanding and implementing effective work design principles, organizations can create a productive and satisfying work environment, which ultimately supports overall business success.